Analisis Pre Marital Screening sebagai Upaya Pencegahan Stunting di Kota Jambi - Sri Astuti Siregar; Asparian Asparian; Usi Lanita; La Ode Reskiaddin (Universitas Malahayati Lampung, 2024)
ABSTRACT Indonesia is still working hard to overcome the stunting problem. Even though there has been a decline, further efforts are still needed to achieve the national target of 14% in 2024. Prospective brides are one of the target groups in implementing the acceleration of stunting reduction.Pre marital screening or pre-marital examination is a preventive measure that must be taken to prevent health problems for oneself, one's partner, or one's offspring in the future. This research uses quantitative methods with a cross-sectional approach. Random samplingproportional simple random sampling from 11 sub-districts in Jambi City, there were 81 prospective brides and grooms. There is a significant relationship between education (p-value=0.016), knowledge (p-value=0.009), and attitude (p-value=0.026) on the implementation of Pre Marital Screening. While the age variable (p-value=0.279) does not show a significant relationship with the implementation of Pre Marital Screening. Therefore, there needs to be a collaborative effort to improve services to bride and groom, so that implementation Pre Marital Screening is not only considered as one of the pre-marital administrative documents. Keywords: Premarital Screening, Catin, Stunting ABSTRAK Indonesia hingga kini masih bekerja keras untuk mengatasi masalah stunting. Meskipun mengalami penurunan, masih diperlukan upaya lebih lanjut untuk mencapai target nasional 14% di tahun 2024. Calon pengantin (Catin) merupakan salah satu kelompok sasaran dalam pelaksanaan percepatan penurunan stunting. Pre marital screening atau pemeriksaan pra nikah merupakan sebuah tindakan pencegahan yang wajib dilakukan untuk mencegah terjadinya permasalahan kesehatan pada diri sendiri, pasangan, maupun keturunan kedepannya Penelitian ini menggunakan metode kuantitatif dengan pendekatan cross sectional. Pengambilan sampel secara proportional simple random sampling dari 11 Kecamatan di Kota Jambi berjumlah 81 calon pengantin. Terdapat hubungan yang signifikan antara pendidikan (p-value=0,016), pengetahuan (p-value=0,009), dan sikap (p-value=0,026) terhadap pelaksanaan Pre Marital Screening. Sementara variable umur (p-value=0,279) tidak menunjukkan adanya hubungan signifikan dengan pelaksanaan Pre Marital Screening. Oleh sebab itu, perlu adanya upaya kolaboratif dalam meningkatkan pelayanan kepada Catin, sehingga pelaksanaan Pre Marital Screening tidak hanya dianggap sebagai salah satu kelengkapan berkas administratif pra nikah. Kata Kunci: Pre Marital Screening, Catin, Stunting